The genetics and epidemiology of neuropathic pain-like symptoms in people with osteoarthritis and post-total joint replacement - Warner, Sophie Catriona (2016)
Background: Osteoarthritis (OA) is the most common form of arthritis and one of the leading causes of pain and disability worldwide. The only long-term treatment for severe, end-stage OA is removal of the damaged tissues by a total joint replacement (TJR). However for some individuals, pain continues to be a concern post-TJR. As well as this, a proportion of individuals with OA and post-TJR suffer with neuropathic pain-like symptoms (NP). NP is caused by changes or damage to the nervous system, which can occur as a result of nerve injury or chronic pain. NP differs from nociceptive pain in that symptoms can occur in response to a non-harmful stimulus, or in the absence of a stimulus. It is also hard to treat NP effectively. The molecular mechanisms underlying pain and NP in OA are still not well understood and therefore require further study. The high prevalence of OA means research in this field has the potential to impact many individuals.